257. Workplace Safety: Risks assessment of electromagnetic fields exposure. (December 2018) - Paoli, M.; Sani, L.; Vispa, A.; Raspa, G.; Tiberi, G.; Angelucci, M.; Ceccarelli, D.
Abstract : Purpose: The European Directive 2013/35/UE, implemented in Italy by Legislative decree 159 dated 1 August 2016, introduces new exposure limits and it modifies the procedures for evaluating the exposure of workers to electromagnetic fields. Since June 2016, UBT srl, in collaboration with ARPA Umbria, has analyzed the issues recalled by the new Directive. In particular, this study focuses on investigating the instrumentation for performing electromagnetic fields measurements and on drafting of guidelines for standard assessment of electromagnetic fields exposure. Methods: The devices here analyzed are magnetotherapies, electrosurgical units, welders, magnetizers, radio frequency dryers and test banks, both in healthcare and in general work environments. The instruments, used for measurements, are broadband probes from different manufacturers and with different characteristics. The data analysis method was chosen based on frequencies and waveform of electromagnetic radiations generated by different kinds of devices; specifically, the weighted peak method has been used. Results: The measurements highlight different and complex exposure conditions based on the type of source (i.e. device) and workplace. In the case of magnetotherapy rooms, the worker's weighted peak index was lower than unit; whereas, in the same rooms, general public limits can be exceeded 4 times also. Regarding welders and electrosurgical units, the exposure conditions were more complex and, before evaluation, a detailed analysis of radiation source was required. Conclusions: The exposure assessment showed the necessity to delimit the area and/or to use dedicated warning signs so that non-exposed workers or the general public (for example, people accompanying patients) don't have access to areas in which exposure limits are higher than the action levels. Finally, professional training is fundamental in preventing risks[1] .